IMPROVING STUDENT’S LEARNING ACHIEVEMENT ON MATHEMATICS THROUGH COOPERATIVE LEARNING TYPE THINK PAIR SHARE (TPS) - Rini Setyaningsih; Sri Rejeki (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
This study aims to find out the significant effect of cooperative learning type Think Pair Share (TPS) in improving students’ learning achievement on the subject of elementary statistics. This is a quasi experimental study involving all students who take elementary statistics subject at the Department of Mathematics Education, Universitas Muhammadiyah Surakarta. The subjects of this study were devided into 2 groups, namely the experimental group taught using cooperative learning type Think Pair Share (TPS) and the control group taught using conventional learning. Each group is taught with the same topic, namely hypothesis testing. In this study, the data collection was done by test and observation. Whereas, the data analysis was conducted using one way ANOVA (Analysis of Variance) with five percent of significant level.  Based on the analysis, it can be concluded that there is a significant effect of learning methods on students’ learning achievement on statistics. The learning mathematics with cooperative learning type Think Pair Share (TPS) can improve students’ learning achievement on statistics